CEREBROSPINAL FLUID FLOW DYNAMICS THROUGH THE CEREBRAL AQUEDUCT IN HEALTHY ADULTS: A 3.0 TESLA PHASE-CONTRAST MRI STUDY (Vietnam Journal of Community Medicine, 2026)
Purpose: To describe cerebrospinal fluid (CSF) flow characteristics through the cerebral aqueduct using 3.0 Tesla phase-contrast MRI and to evaluate their associations with age and sex. Methods: A cross-sectional descriptive study was conducted on 20 healthy adults who underwent brain MRI with an additional phase-contrast sequence at Hanoi Medical University Hospital from May 2025 to March 2026. The analyzed parameters included peak systolic velocity, peak diastolic velocity, systolic volume, diastolic volume, flow, and stroke volume. Results: The mean peak diastolic and systolic velocities were 5.79 ± 2.06 cm/s and 5.29 ± 2.00 cm/s, respectively. The mean diastolic and systolic volumes were 0.029 ± 0.017 ml and 0.030 ± 0.023 ml. Mean flow was close to zero (-0.0003 ± 0.0099), while stroke volume was 29.0 ± 18.91. No statistically significant correlations were found between age and CSF flow parameters (p > 0.05), although stroke volume showed a positive trend with age (rho = 0.383; p = 0.096). No significant differences were observed between males and females (p > 0.05). Conclusion: Phase-contrast MRI at 3.0 Tesla provides a non-invasive method for quantifying CSF flow through the cerebral aqueduct, offering preliminary reference data and supporting clinical evaluation of CSF circulation disorders.
Keywords: cerebrospinal fluid, cerebral aqueduct, phase-contrast MRI, 3.0 Tesla, CSF dynamics.